2009
DOI: 10.1002/marc.200900209
|View full text |Cite
|
Sign up to set email alerts
|

From Nanodot to Nanowire: Hybrid Au/Titania Nanoarrays by Block Copolymer Templates

Abstract: A simple scheme to fabricate 2-D arrays of Au/titania hybrid nanopatterns is presented, using polystyrene-block-poly(ethylene oxide) diblock copolymer (PS-b-PEO) as templates coupled with sol-gel chemistry. Both the functionalized Au nanoparticles (NPs) and titania precursors are selectively incorporated into the PEO domain. A series of morphologies ranging from nanodot to nanowire arrays is formed and the mechanism of morphological evolution is discussed. Such hybrid films exhibit characteristic localized sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Figure b displays elongated nanostructures of 15 nm in width composed of individual grains of about 3–4 nm in diameter. These grains exhibit a more compact nature as compared to other reports describing the preparation of nanopatterns via the assembly of nano-objects directed by templating molecules. , , Selected area electron diffraction (SAED) indicates the polycrystalline nature of the nanostructures randomly oriented on the SiO x membrane (Figure c). The Debye–Scherrer inner ring shows a lattice plane spacing of around 3.5 Å, which corresponds to the lattice spacing for the (101) plane of anatase, thus excluding the presence of the rutile phase.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Figure b displays elongated nanostructures of 15 nm in width composed of individual grains of about 3–4 nm in diameter. These grains exhibit a more compact nature as compared to other reports describing the preparation of nanopatterns via the assembly of nano-objects directed by templating molecules. , , Selected area electron diffraction (SAED) indicates the polycrystalline nature of the nanostructures randomly oriented on the SiO x membrane (Figure c). The Debye–Scherrer inner ring shows a lattice plane spacing of around 3.5 Å, which corresponds to the lattice spacing for the (101) plane of anatase, thus excluding the presence of the rutile phase.…”
Section: Resultsmentioning
confidence: 73%
“…Despite the low boiling point of water in comparison to BnOH, the formation of quasi-hexagonally ordered TiO 2 nanoarrays was possible by performing EISA at 100 °C and room temperature with the difference that particles were more laterally separated in the latter case (Figure S4a,b). As other groups observed the opposite morphological transition by increasing the concentration of titanium precursor, , we prepared a solution containing three times more TiCl 4 , which led us to observe arrays of parallel TiO 2 nanowires even after 10 weeks of aging (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…A similar approach has been used to generate SiO 2 and TiO 2 nanostructures with reverse morphology and mesoporous TiO 2 thin films using nanostructured BCP films as templates. [57][58][59] Russell's group showed that alkali halide or metal salts complexed with the poly(ethylene oxide) (PEO) blocks in thin films of PS-b-PEO, on the order of a few ions per chain. 60 They demonstrated large flexibility in the choice of salt used, including gold or cobalt This journal is c The Royal Society of Chemistry 2013 salts such that well-organized patterns of nanoparticles can be generated inside the PEO microdomains upon exposure to the electron beam.…”
Section: In Situ Synthesis Of Nanoparticles In Bcp Microdomainsmentioning
confidence: 99%
“…[1][2][3][4] The self-assembly (SA) of BCPs into regularly sized and spaced nanoscopic elements makes them suitable candidates to create periodic matrices, whilst incorporation of specic nanoparticles (NPs) into the selective BCP domain leads to the formation of an organic-inorganic hybrid with distinct target properties. [5][6][7][8][9][10] Such BCP induced nanoarrays composed of metal or metal oxide have found wide applications in areas such as sensor devices, 11 photocatalysis [12][13][14] and photovoltaic devices. 15 Among the BCP assisted inorganic nanostructures, nanowire patterns were found to be attractive owing to their enhanced properties over their nanodot counter parts.…”
Section: Introductionmentioning
confidence: 99%